Nilai Tambah Produk Olahan Perikanan pada Industri Perikanan Tradisional di DKI Jakarta - Popong Nurhayati (Buletin Ekonomi Perikanan, 2004)
In general, value added could describe some aspects, especially production and marketing aspects like supply of resources (as raw material in processing activity), number of employees, price of products, and trend of consumer behavior. In more specific, counting value added also related to the margin and the remuneration of employees.The method used in this research is survey. Purposive sampling technique is utilized in sampling method. Research was conducted by using the primary data from the processors and traders of traditional processing of fisheries products in Kelurahan Muara Angke and Kelurahan Pluit. The secondary data used in this research are statistical reports and yearly reports of Oinas Perikanan OKI Jakarta.The objectives of this research are 1) to examine the value added of traditional processed of fisheries products in OKI Jakarta, 2) to examine the implication of value added of traditional processed of fisheries products.This research shows that the 9 traditional processed of fisheries products have differentiation in amount of added value. Salting of kakap and tanning of skin of pari are two kinds of traditional processing of fisheries products that have bigger amount ofadded value. Added value of Salting of kakap is Rp 12854.48 and tanning of skin of pari have an added value Rp 8 919.44. Other traditional processed of fisheries productshave an added value less then Rp 4000.00.